Dynamic life and death interactions between Mycobacterium smegmatis and J774 macrophages - Anes, E (2015)
After internalization into macrophages non-pathogenic mycobacteria are killed within phagosomes. Pathogenic mycobacteria can block phagosome maturation and grow inside phagosomes but under some conditions can also be killed by macrophages. Killing mechani